Plankton Planet: A frugal, cooperative measure of aquatic life at the planetary scale - Colomban de Vargas; Noan Le Bescot; Thibaut Pollina; Nicolas Henry; Sarah Romac; Sébastien Colin; Nils Haëntjens; Margaux Carmichael; Calixte Berger; David Le Guen; Johan Decelle; Frédéric Mahé; et al. (Frontiers in Marine Science, 2022)
In every liter of seawater there are between 10 and 100 billion life forms, mostly invisible, called marine plankton or marine microbiome, which form the largest and most dynamic ecosystem on our planet, at the heart of global ecological and economic processes. While physical and chemical parameters of planktonic ecosystems are fairly well measured and modeled at the planetary scale, biological data are still scarce due to the extreme cost and relative inflexibility of the classical vessels and instruments used to explore marine biodiversity. Here we introduce ‘Plankton Planet’, an initiative whose goal is to engage the curiosity and creativity of researchers, makers, and mariners to ( i ) co-develop a new generation of cost-effective (frugal) universal scientific instrumentation to measure the genetic and morphological diversity of marine microbiomes in context, ( ii ) organize their systematic deployment through coastal or open ocean communities of sea-users/farers, to generate uniform plankton data across global and long-term spatio-temporal scales, and ( iii ) setup tools to flow the data without embargo into public and explorable databases. As proof-of-concept, we show how 20 crews of sailors were able to sample plankton biomass from the world surface ocean in a single year, generating the first seatizen-based, planetary dataset of marine plankton biodiversity based on DNA barcodes. The quality of this dataset is comparable to that generated by Tara Oceans and is not biased by the multiplication of samplers. The data unveil significant genetic novelty and can be used to explore the taxonomic and ecological diversity of plankton at both regional and global scales. This pilot project paves the way for construction of a miniaturized, modular, evolvable, affordable and open-source citizen field-platform that will allow systematic assessment of the eco/morpho/genetic variation of aquatic ecosystems and microbiomes across the dimensions of the Earth system.